2023
DOI: 10.3390/biom13010103
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Models of Ovarian Cancer: Bridging the Gap between Pathophysiology and Mechanistic Models

Abstract: Ovarian cancer (OC) is a disease of major concern with a survival rate of about 40% at five years. This is attributed to the lack of visible and reliable symptoms during the onset of the disease, which leads over 80% of patients to be diagnosed at advanced stages. This implies that metastatic activity has advanced to the peritoneal cavity. It is associated with both genetic and phenotypic heterogeneity, which considerably increase the risks of relapse and reduce the survival rate. To understand ovarian cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 160 publications
0
6
0
Order By: Relevance
“…This approach has stimulated the development of novel detection platforms for ovarian cancer biomarkers, offering renewed hope for patients with complex tumors refractory to conventional protocols. A typical method for constructing an in vitro model of ovarian cancer is to use matrix-coated culture dishes and media as spherical or tumor explants to promote cancer cell proliferation [ 262 ]. Microfluidic spherical culture presents a promising alternative with micro-cancer dimensions, minimizing the cell requirement during initiation, and ensuring stability, and consistency in drug response [ 263 ].…”
Section: Microfluidic Chips For Gynecological Diseasesmentioning
confidence: 99%
“…This approach has stimulated the development of novel detection platforms for ovarian cancer biomarkers, offering renewed hope for patients with complex tumors refractory to conventional protocols. A typical method for constructing an in vitro model of ovarian cancer is to use matrix-coated culture dishes and media as spherical or tumor explants to promote cancer cell proliferation [ 262 ]. Microfluidic spherical culture presents a promising alternative with micro-cancer dimensions, minimizing the cell requirement during initiation, and ensuring stability, and consistency in drug response [ 263 ].…”
Section: Microfluidic Chips For Gynecological Diseasesmentioning
confidence: 99%
“…4 According to a global research published by the International Federation of Gynecology and Obstetrics (FIGO), the prevalence of OC is increasing in younger women, although various investigations have outlined that these young women are interested in preserving their fertility in addition to treating this cancer but it is difficult to sustain the reproductive function because the ovary is site of the primary cancer. 3,5 Due to the lack of specificity and sensitivity of CA125 marker, widely used for the detection of this fatal disease, highly efficient, specific and sensitive marker is prerequisite in reducing both cancer incidence as well as mortality. 6,7 The biological mechanism for transforming normal cells into cancerous ones remains elusive, although increasing evidence signifies that this transformation likely involves the accumulation of genetic lesions in at least three classes of genes, namely proto-oncogenes, tumor suppressor genes, and mutator genes.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences report that the family history of OC is associated with increased risk of this disease 4 . According to a global research published by the International Federation of Gynecology and Obstetrics (FIGO), the prevalence of OC is increasing in younger women, although various investigations have outlined that these young women are interested in preserving their fertility in addition to treating this cancer but it is difficult to sustain the reproductive function because the ovary is site of the primary cancer 3,5 . Due to the lack of specificity and sensitivity of CA125 marker, widely used for the detection of this fatal disease, highly efficient, specific and sensitive marker is prerequisite in reducing both cancer incidence as well as mortality 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…A6β1 and α2β1 represent other integrins containing the β1 subunit that are also related to spheroid formation, binding laminin and collagen, respectively. The vitronectin/αv-integrin adhesion system is also implicated in spheroid formation [ 23 ]. Carduner et al confirmed that αv-integrin diminution in spheroids is associated with decreased ERK 1/2 activation and the induction of apoptosis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The epithelial–mesenchymal transition is a morphogenetic process of cellular plasticity, where epithelial cells deviate from their epithelial phenotype (apical–basal polarity, cell–cell, and cell–ECM adhesion) and transit to a mesenchymal morphology [ 27 ]. Although this shift takes place physiologically in embryonic development, where epithelial and neuroectodermal cells acquire the capacity to migrate and drive the formation of multiple cell types, it also takes part in pathophysiological processes, such as healing, fibrosis, and cancer [ 23 , 28 ]. In the latter, it orchestrates some of its deadliest hallmarks (invasion, metastasis formation, and chemoresistance) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%